The Influence Of Product Diversity, Availability, Promotion, And Service Quality On Customer Satisfaction At The Nova Shop In The Hamlet Of Kampung Jawa - Bayu, Sartika; Broto, Bayu Eko (PT ARRUS Intelektual Indonesia, 2025)
This study focuses on analyzing the impact of several factors, namely product diversity, product availability,promotion, and service quality, on consumer satisfaction at Toko Nova, Kampung Jawa. The research adopts a quantitative approach using a survey method to collect data from 100 respondents through questionnaires. Multiple linear regression analysis is applied to test the relationship between independent and dependent variables in this study. The findings show that, simultaneously, the four independent variables have a significant effect on consumer satisfaction, with a coefficient of determination (R²) of 72.7%. The study further reveals that, partially, product diversity and service quality significantly influence consumer satisfaction. Product diversity is the dominant factor in enhancing consumer satisfaction, followed by service quality. Meanwhile, promotion and product availability do not show a significant effect. These findings suggest that strategies aimed at increasing product variety and improving service quality are key to enhancing customer satisfaction in traditional retail stores.